Perception on Collaborative Writing, Self-efficacy and Writing Achievement in Information Technology Era : A Correlational Study - Abdul Aziz; Khoirul Anwar; Slamet Asari (Jetlal, 2023)
This mix method study investigated the correlation among students’ perception on collaborative writing (SPoCW), students’ self-efficacy (SSE) and students’ writing achievement (SWA). The quantitative data of the study was gained from 62 students who have been taught using collaborative writing during one semester. The data included the students’ perception on collaborative writing questionnaire adapted from [1]. The questionnaire consisted of 18 statements with a five Likert scales. The reliability is 0.892. While students’ self-efficacy is measured using self efficacy questionnaire consists of 23 statements adopted from [2] with the reliability is 0.80. Using correlation Pearson Product Moment, It was found that SPoCW correlated with SSE and the score is 0.377. To investigate the correlation between independent variable (SPoCW and SSE) and dependent variable (SWA), the researcher used Analysis Model Summary, it showed that R Square value is 0.394. This mean that the effect of SPoCW and SSE toward students writing achievement is 39.4 % and the rest is influenced by another factor. While to get qualitative data, semi structure interview was randomly given to the students and it was revealed that mostly students felt confident and had a new writing experience with collaborative writing which strengthen the investigation. It is recommended to build good students’ perception and self-efficacy for best writing achievement.